Measuring the impact of agricultural production shocks on international trade flows - Shon Ferguson; Johan Gars (Research Institute of Industrial Economics (IFN), 2018)
The purpose of this study is to measure the sensitivity of traded quantities and trade unit values to agricultural production shocks. We develop a general equilibrium model of trade in which production shocks in exporting countries affect both traded quantities and trade unit values. The model includes per-unit trade costs and develops a methodology to quantify their size exploiting the trade unit value data. Using bilateral trade flow data for a large sample of countries and agricultural commodities we find that the intensive margin of trade is relatively inelastic to production shocks, with a 1 percent increase in production leading to a 0.5 percent increase in exports. We also find that per-unit trade costs are large, comprising 15 to 20 percent of import unit val- ues on average. Overall, our results suggest that there is room for improving trade as a mechanism for coping with food production volatility.
Keywords: F14; F18; Q11; Q17; Q18; 330; Food production volatility; Trade costs; Agricultural trade; Gravity model